PENGARUH LOCUS OF CONTROL DAN HARGA DIRI TERHADAP MOTIVASI KERJA PEGAWAI DINAS PENDIDIKAN KOTA MEDAN - Masrul Badri; Azhar Aziz (Universitas Medan Area, 2011)
This study aims to see the effect of locus of control and dignity of the employee work motivation Medan City Department of Education. Based on the existing theoretical framework, namely by Burns (2004) states that individuals are not easily affected by external environment of an individual who himself is having internal Locus Of Controln Then the proposed hypothesis: 1). There is the influence of Locus of control and self-esteem together on employee motivation employee Education Department. 2). There is the influence of self-esteem of employee motivation. 3). There is the influence of locus of control on employee motivation. In proving the above hypothesis, we used data analysis methods, namely Multiple Regression Analysis.. Based on these results, the hypothesis proposed been accepted. 2) As for the contribution of the variable influence of self-esteem on the work motivation of employees by 29%. 3). Effect of locus of control on employee motivation to work in Medan City Government Department of Education with a contribution of 47%. The total effective contribution of these two independent variables (locus of control and self-esteem) on the performance of employees is 76% From the results it is known that there is still a 24% influence of other factors of motivation to work is not examined in this study.